Current Switching Coupled to Molecular Spin‐States in Large‐Area Junctions. Issue 34 (16th June 2016) - Lefter, Constantin; Rat, Sylvain; Costa, José Sánchez; Manrique‐Juárez, María D.; Quintero, Carlos M.; Salmon, Lionel; Séguy, Isabelle; Leichle, Thierry; Nicu, Liviu; Demont, Philippe; Rotaru, Aurelian; Molnár, Gábor; et al.
Abstract : The fabrication of large‐area vertical junctions with a molecular spin‐crossover complex displaying concerted changes of spin degrees of freedom and charge‐transport properties is reported. Fabricated devices allow spin‐state switching in the spin‐crossover layer to be triggered and probed by optical means, while detecting associated changes in electrical resistance in the junctions.